2020
DOI: 10.1007/s10640-020-00446-9
|View full text |Cite
|
Sign up to set email alerts
|

Building a Social Mandate for Climate Action: Lessons from COVID-19

Abstract: The COVID-19 imposed lockdown has led to a number of temporary environmental side effects (reduced global emissions, cleaner air, less noise), that the climate community has aspired to achieve over a number of decades. However, these benefits have been achieved at a massive cost to welfare and the economy. This commentary draws lessons from the COVID-19 crisis for climate change. It discusses whether there are more sustainable ways of achieving these benefits, as part of a more desirable, low carbon resilient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(72 citation statements)
references
References 27 publications
0
72
0
Order By: Relevance
“…A last research theme among the 440 documents identified by the searches of the databases focuses on the future tasks that we, as a society, and environmental researchers, must develop to mitigate climate change. Howarth et al (2020) , for example, posit that COVID-19 has raised our awareness of how vulnerable we are in the face of climate change. According to these authors, mitigating climate change requires a more carefully planned, inclusive, less disruptive and greater sustained response through deliberative engagement mechanisms aiming to build a social mandate for post-COVID climate action.…”
Section: Resultsmentioning
confidence: 99%
“…A last research theme among the 440 documents identified by the searches of the databases focuses on the future tasks that we, as a society, and environmental researchers, must develop to mitigate climate change. Howarth et al (2020) , for example, posit that COVID-19 has raised our awareness of how vulnerable we are in the face of climate change. According to these authors, mitigating climate change requires a more carefully planned, inclusive, less disruptive and greater sustained response through deliberative engagement mechanisms aiming to build a social mandate for post-COVID climate action.…”
Section: Resultsmentioning
confidence: 99%
“…The major contribution of the current study is the preliminary exploratory evidence of a potential positive association between the risk perception of the pandemic and climate change, one of the most urgent environmental problems of our time, as well as psychological mechanism underlying this association. Our results revealed that pandemic risk perception does have positive association with climate change concern, implying that not only the governments have increased their concern for climate change as well as awareness of green socioeconomic recovery 5,16,17 , but the general public have also raised their awareness of and attention to climate change, and this relationship is partially mediated by pandemic-aroused negative emotions. These results highlight the importance of emotional pathway in linking pandemic and climate change concern, and we suggest taking these public emotional responses as an opportunity to strengthen climate education.…”
Section: Discussionmentioning
confidence: 71%
“…Among the multiple impacts this pandemic has caused to the whole society, one striking focus of academic assessment and evaluation is climate change 5 which has been declared as one of the major issues of our time by the United Nations. With dramatically declined transport and altered pattern of consumption due to home con nement, by early April 2020, daily global annual CO 2 emissions was estimated to have decreased by 17% compared with the 2019 mean level (if some social restrictions could remain to the end of this year, the annual CO 2 emissions could be reduced by up to 7%) 6 and the emission fall would be more than any year on record 7 , while NO x emissions also declined by as much as 30%, contributing to a cooling effect as well 8 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations